Prognostic impact of vascular invasion in differentiated thyroid carcinoma: a systematic review and meta-analysis. Issue 2 (August 2017) - Vuong, Huy Gia; Kondo, Tetsuo; Duong, Uyen N P; Pham, Thong Quang; Oishi, Naoki; Mochizuki, Kunio; Nakazawa, Tadao; Hassell, Lewis; Katoh, Ryohei
Abstract : Background: The role of vascular invasion (VI) as a prognostic marker in thyroid cancer is continuously debated among investigators. In this systematic review and meta-analysis, we aimed to investigate the association of VI with tumor recurrence and patient mortality in differentiated thyroid cancers (DTCs). Methods: We searched five electronic databases for cases of DTC matching our criteria. Data of tumor persistence, locoregional recurrence (LRR), distant recurrence (DR) and overall recurrence/persistence (RP) were extracted and pooled into odds ratios (OR) and corresponding 95% confidence intervals (CIs) using random effect model. Pooled hazard ratio (HR) for disease-specific survival (DSS) was calculated using random effect model weighted by inverse variance method. Publication bias was examined by using Egger's test and funnel plot. Results: From 1650 studies, we included 26 studies comprising 11 961 DTCs for meta-analyses. In DTC patients, we found significant associations of VI with tumor persistence (OR = 2.75; 95% CI = 1.46–5.18), LRR (OR = 4.44; 95% CI = 2.94–6.71), DR (OR = 5.08; 95% CI = 2.95–8.75), overall RP (OR = 3.53; 95% CI = 2.09–5.96) and worse DSS (HR = 2.47; 95% CI = 1.45–4.21). Our results also demonstrated that the presence of extensive VI is associated with a significantly higher risk for DR in follicular thyroid carcinomas as compared with focal VI. Conclusion: Our study demonstrated a significant impact of VI on tumor recurrence and patient survival in DTC patients. The presence and extent of VI should be considered an adverse prognostic factor in DTCs.